1975
DOI: 10.1002/jpln.19751380609
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Microbial Fertilizers. III. Effect of phosphate and silicate dissolving bacteria on the uptake of phosphorus and potassium from calcareous soils by sorghum helepensis

Abstract: Einfluß von phosphat‐ und silikat‐auflösenden Bakterien auf die P‐ und K‐Aufnahme von Sorghum helepensis aus kalkhaltigen Böden.. Der Einfluß einer kombinierten Impfung mit phosphat‐ und silikatauflösenden Bakterien (Bacillus megaterium var. phosphaticum bzw. Bacillus sp) auf die P‐ und K‐Aufnahme von Sorghum helepensis wurde in Topfversuchen ermittelt. Als Substrat dienten kalkhaltige Böden mit 25,54 bzw. 96% CaCO3. Während kombinierte Impfung die K‐Aufnahme nicht beeinflussen konnte, wurde die P‐Aufnahme in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…phosphaticum has been used as microbial fertilizer (Phosphobactrin) and applied to millions of hectares in Europe and the Soviet Union (Cooper, 1959) to increase P availability to a variety of crops. Moreover, several investigators have reported increases in yields of different crops 181 as a result of Phosphobacterin application to calcareous soils (Kabesh et al, 1975;Osman et al, 1974;Saber et al, 1975). More attention has apparently given to the role of phosphate-dissolving bacteria (PDB) than that of phosphate dissolving fungi (Agnihorti, 1970;Barthakur, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…phosphaticum has been used as microbial fertilizer (Phosphobactrin) and applied to millions of hectares in Europe and the Soviet Union (Cooper, 1959) to increase P availability to a variety of crops. Moreover, several investigators have reported increases in yields of different crops 181 as a result of Phosphobacterin application to calcareous soils (Kabesh et al, 1975;Osman et al, 1974;Saber et al, 1975). More attention has apparently given to the role of phosphate-dissolving bacteria (PDB) than that of phosphate dissolving fungi (Agnihorti, 1970;Barthakur, 1978).…”
Section: Introductionmentioning
confidence: 96%
“…The inoculum was mixed with the surface soil. Counting of phosphate dissolving bacteria was carried out in the rhizosphere soil on modified Bunt and Rovira medium (1955) initially and at intervals of 15 days as described by Saber et al (1975).…”
Section: Methodsmentioning
confidence: 99%
“…The estimated profitability of the each pound spent on remediating agricultural drainage water is given in ( Zaghloul, 2016;Zayed et al, (1971), Monib et al, (1971), Abd-el-Malek et al, (1972, Guirguis et al, (1972, Zanati et al, (1973), Saber et al, (1974), Saber et al, (1975a, Kabesh et al, (1975), Saber (1976a,b,c,d) Mansour et al, 2022). Our present study exhibit that, the combined application of water remediation using DHS as well as soil remediation using microbial amendments has profound effects on soil yield productivity with the less agricultural demands needed that usually used during the traditional agriculture process.…”
Section: Profitability Of the Pound Spent On The Remediation Of Agric...mentioning
confidence: 99%